Avaliação da eficiência de sedimentação em função da resistência, ruptura e recrescimento de flocos obtidos a partir de água com turbidez elevada - Silva, Lorena Miranda de Almeida (2018)
The purpose of this work was to evaluate the sedimentation efficiency as a function of the resistance, rupture and regrowth of floc obtained from water with high turbidity using sodium aluminate as a chemical coagulant. The coagulation, flocculation and decantation processes were simulated in Jar Test bench equipment. The study water was produced with the addition of kaolinite in distilled water, providing turbidity of 50 UNT. The first stage of the research consisted of producing coagulation / flocculation diagrams for sedimentation speeds (Vs) of 5; 2.5; 1 and 0.5 cm / min and determined the ideal coagulant dosage pair x coagulation pH favorable to the removal of turbidity. The coagulant dosage adopted for the next step was 70 mg / L, which allowed a removal greater than 97% for a pH range of 8.23 ± 0.05. In the second stage of the research, the flocculation was monitored by a non-intrusive methodology based on the acquisition of images of the floc in the plane of light incident in the jar established by laser. In which the influence of rupture and regrowth on the sedimentability of the floc was evaluated. It started with a fast mixing time of 10 s and a mixing gradient of 800 s-1, followed by flocculation for different speed gradients (Gf = 20, 30, 40, 50 and 60 s-1), in independent experiments, with flocculation time of 20 min. Subsequently, induced rupture was performed, for 10 s, for two rupture speed gradients (Gq = 80 and 200 s-1), and immediately, for refloculation, the initial condition of each of the used flocculation gradients was reestablished, with reflux time of 20 min. Finally, both in the flocculation and refloculation stages, sample collections were performed for the same Vs as in the first stage, in order to assess the efficiency of turbidity removal. The computational treatment of the images was performed with the aid of the free software ImageJ J1.51 to obtain the particle size distribution (DTP) and parameter β, representative of the DTP; evolution of the stable diameter (d) to analyze the recovery of the floc size and recovery ratio (RR); evaluation of the strength factor (FR) and the theoretical value of the floc strength (local tension - σ). It was concluded that higher velocity gradients are responsible for generating a DTP with a higher concentration of particles in the smaller diameter classes, a behavior confirmed by the study of parameter β and parameter d. Conversely, FR and σ have increasing trends in response to the rise in the speed gradient. After induced rupture, the flocs lost their ability to recover their initial size, so that the higher the Gq, the lower the recovery, regardless of Gf. In the same way, the removal of turbidity was compromised by the elevation of Gf, as well as after undergoing induced rupture, so that the increase in Gq further promoted the loss of removal efficiency. Therefore, the increase in Gf is more expressive in the sedimentation changes of the flocs than the intensity of Gq. For lower sedimentation speeds, the removal efficiency was more affected by the elevation of the flocculation gradient than by the interference of the induced rupture the flocs process. In general, the best results were shown for the 20 s-1 flocculation gradient.